Securities financing transactions and the (re)use of collateral in Europe – An analysis of the first data collection conducted by the ESRB from a sample of European banks and agent lenders - Joachim Keller; Antoine Bouveret; Cristina Picillo; Zijun Liu; Julien Mazzacurati; Philippe Molitor; Jonas Söderberg; John Theal; Francesco de Rossi; Romain Calleja (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2014)
Securities financing transaction (SFT) markets and the management and usage of collateral are elements of the financial system which are of systemic relevance. As such, there is a clear need for enhanced transparency and regulatory oversight. The European Systemic Risk board (ESRB) mandated a task force to identify the potential risks related to SFTs in Europe and to develop policy proposals to better monitor any vulnerabilities identified by the analysis. This report presents the results of two data collection exercises that were conducted to gain some initial insights into the structure of the SFT market and the correlated practices adopted by market participants concerning the re-investment or the re-use of the collateral sourced through SFTs or via equivalent transactions. A description of this landscape is, in fact, crucial as a first step in assessing the risks emanating from the cash and securities collateral markets and their potential implications for macro-prudential policy in Europe. By providing a description of the SFT landscape, the data collection exercises undertaken by the ESRB have a macro-prudential dimension in that they provide data at an aggregated level. The first data collection exercise encompassed a sample of 38 EU banks, representing approximately 60% of the EU banking system's total assets. The institutions covered by this sample are the main players in the management of securities collateral. The second data collection targeted 13 agent lenders that are considered to be the largest re-investors of cash collateral in Europe. The sample period of the data is fixed at the end of February 2013. The ESRB templates yielded a unique set of data on the sources and use of securities collateral (non-cash collateral) by banks, as well as on the re-investment of cash collateral by agent lenders. The data collections were intended to fit in the broader policy context initiated by the Financial Stability Board (FSB) and the resulting analyses ultimately address a number of theFSB's recommendations. The first element of the analysis in this report is specifically related to the FSB's fourth recommendation (disclosure of collateral management activities) (FSB, 2013) and, to a certain extent, to the first recommendation (authorities to collect granular information on SFTs of large international financial institutions). The second element is similarly related to the first of the FSB's recommendations, but also the sixth, which requests better disclosure ofsecurities lending activities. The analysis contained thereafter is relevant for the European Commission's proposal on the reporting of SFTs to trade repositories (EC, 2014), which will greatly enhance transparency and regulatory oversight of SFT activities in the European Union. Finally, the report is in line with the ESRB's outline of a monitoring framework (ESRB, 2013).
Keywords: G15; G18; 330; secruties financing transactions; systemic risk; transparency; regulatory oversight